Manejo y disposición final de desechos infecciosos y corto punzantes que se generan en el Centro de Salud Balsapamba periodo julio-diciembre 2016. - Lata Quinatoa, Jessica Vanesa (2017)
At the BALSAPAMBA HEALTH CENTER, we have demonstrated an inadequate management of collection, transport and storage of infectious and sharps waste by staff working in the Health Unit; Therefore we have seen the need to carry out the research work in this institution, where we obtain results through different methods such as observation and the application of surveys to those who work in this health home. The results obtained indicate that there is a high rate of inadequate waste management by approximately 49.5%. In the face of this problem, our intervention plan is aimed at implementing an infectious waste management protocol for this Health Center and proposing a circle of continuous improvement in order to improve the knowledge of the INTERMINISTERIAL REGULATION FOR THE INTEGRAL MANAGEMENT OF SANITARY WASTES.